Fracture resistance of zirconia‐based all‐ceramic crowns after bur adjustment - Rues, Stefan; Schwindling, Franz Sebastian; Meyer, André; Rammelsberg, Peter; Schmitter, Marc (European journal of oral sciences, 2017)
Abstract Intra‐oral grinding is often required to optimize occlusion of all‐ceramic restorations. The effect of burs of different grit size on the fracture resistance of veneered zirconia crowns was investigated in this study. Forty‐eight standardized zirconia copings were produced. The ceramic veneer was designed with a positive ellipsoidal defect on the palatal aspect of the crowns. To simulate adjustment of dental restorations by burs, this palatal defect was removed by use of three different diamond‐coated burs with grit sizes 46, 107, or 151 μm (fine, medium, or coarse, respectively). Each different grit size of bur was used to grind 16 crowns. All crowns were then polished and surface roughness was measured. Half of the specimens underwent thermomechanical aging (10,000 thermocycles between 6.5°C and 60°C) and 1.2 million cycles of chewing simulation (F = 108 N). A linear regression model was computed to test the effect of aging and grinding grit size at a level of significance of α = 0.05. Fracture loads increased with decreasing grit size. Grit size and aging had a significant effect on the fracture resistance of the crowns. Use of fine and coarse burs for intra‐oral adjustments resulted in different fracture resistance of veneered zirconia crowns. Coarse burs should be avoided in the final stage of grinding before polishing.